METTL16 regulates m6A methylation on chronic hepatitis B associated gene HLA-DPB1 involved in liver fibrosis - Gao, Haibing; Wang, Xiangmei; Ma, Huaxi; Lin, Shenglong; Zhang, Dongqing; Wu, Wenjun; Liao, Ziyuan; Chen, Mengyun; Li, Qin; Lin, Minghua; Li, Dongliang (Frontiers in Genetics, 2022)
The role of genetic factors in the occurrence and progression of chronic hepatitis B (CHB) is still not fully explored. In recent years, genome-wide association studies on CHB patients have demonstrated that a large number of CHB-associated single nucleotide polymorphisms exist in the gene intron, which may regulate expression at the transcriptional level. Modification of RNA m6A methylation is one of the key mechanisms regulating gene expression. Here we show that METTL16, an m6A regulator involved in mRNA intron splicing, is differentially expressed in CHB the tissue of patients who has definite diagnosis of mild and severe fibrosis. At the same time, there are also significant differences in the expression of CHB-associated genes such as HLA-DPA1 and HLA-DPB1. The expression of HLA-DPB1 is related to METTL16. Furthermore, analyses of RNA binding of METTL16 and HLA-DPB1 show that the silencing of METTL16 in astrocytes downregulates m6A and expression of HLA-DPB1. In conclusion, METTL16 participates in the progression of CHB fibrosis by regulating the m6A level and expression of HLA-DPB1.